New insight into IELTS workbook pack [ workbook with answers - akeman; McDowell (Cambridge: Cambridge University Press, 2008)
Instruction covering four exam modules: listening, reading, writing and speaking. Includes one practice test and answer key. Script of accompanying audio recording
To accompany textbook titled "New insight into IELTS workbook pack : workbook with answers / Vanessa Jakeman and Clare McDowell"
COLAL
Keywords: International English Language Testing System -- -- Study guides; Vocabulary -- -- Problems, exercises, etc; English language -- -- Examinations, questions, etc; English language -- -- Spoken English -- -- Problems, exercises, etc